Pathogen surveillance in Southern Ocean pinnipeds - Núñez-Egido, Sandra; Lowther, Andrew; Nymo, Ingebjørg H.; Klein, Jörn; Breines, Eva M.; Tryland, Morten (Polar Research, 2020)
Knowledge of the health status and potential effect of disease outbreaks among Southern Ocean fauna may be decisive for its conservation. We assessed the exposure and infection of Antarctic fur seals (Arctocephalus gazella, AFS) and Southern elephant seals (Mirounga leonine, SES) to parapoxvirus, Phocid alphaherpesvirus-1 (PhHV-1), smooth Brucella spp. and Toxoplasma gondii. AFS (n = 65) serum and swab samples, and SES (n = 13) serum samples from the sub--Antarctic island of Bouvetøya (54°25’S, 03°22’E) were collected during two austral summers (2014/15, 2017/18). Three polymerase chain reaction (PCR) tests amplifying the DNA polymerase, B2L and GIF parapoxvirus genomic regions were performed, investigating DNA from mucosal swab samples. The glycoprotein B gene was targeted to detect PhHV-1 viral DNA. Sera were assayed for T. gondii and smooth Brucella spp. antibodies with indirect enzyme-linked immunosorbent assays. Parapoxvirus PCR amplicons of the expected size were generated in two of the 29 AFS pups (nasal swabs, 2014/15), targeting the B2L (n = 2) and DNA polymerase (n = 1) genes, whereas the GIF PCR did not amplify target sequences. The PCR amplicons were sequenced and blasted in GenBank, revealing highest similarity with a seal parapoxvirus, confirming the presence of the virus in AFS for the first time. No PhHV-1 amplicons were generated, and antibodies against T. gondii or smooth Brucella spp. were not detected. Our data indicate that these seals are host for parapoxvirus but are neither exposed to smooth Brucella spp. nor T. gondii. Evidence of PhHV-1 shedding was not detected.
Keywords: Bouvetøya; Sørishavet; epidemiologi; fylogenetikk; infeksjon; marin biologi; marin zoologi; pelsseler; pinnipedier; serologi; sjøelefanter; virologi

Prey differences drive local genetic adaptation in Antarctic fur seals - Cleary, Alison C; Bester, Marthán; Forcada, Jaume; Goebel, Michael; Goldsworthy, Simon D; Guinet, Christophe; Hoffman, Joseph I; Kovacs, Kit M; Lydersen, Christian; Lowther, Andrew D (Marine Ecology Progress Series, 2019)
Antarctic fur seal (Arctocephalus gazella) colonies are found on sub-Antarctic islands around the continent. These islands experience a range of conditions in terms of physical and biological habitat, creating a natural laboratory to investigate local genetic adaptation. One striking habitat difference is in the availability of Euphausia superba krill as prey, which has led to A. gazella exhibiting a range of diets. A. gazella in some colonies consume exclusively krill, while their conspecifics in other colonies feed mainly on fish and consume few to no krill. To investigate potential adaptations to these different prey fields, reduced representation genome sequencing was conducted on A. gazella from the 8 major colonies. Twenty-seven genomic regions exhibiting signatures of natural selection were identified. Two of these genomic regions were clearly associated with seals living in krill-dominated areas or those in fish-dominated areas. Twenty-two additional genomic regions under selection showed a pattern consistent with prey differences as the driver of selection after historical migrations from krill-dominated habitats where lineages evolved to present krill-poor habitat areas were taken into account. Only 1 of the genomic regions identified appeared to be explained by any other environmental variable analysed (depth). Genomic regions under prey-driven selection included genes associated with regulation of gene expression, skeletal development, and lipid metabolism. Adaptation to local prey has implications for spatial management of this species and for the potential impacts of climate- or harvest-driven reductions in krill abundance on these seals. KEY WORDS: Arctocephalus gazella · Double digest restriction-site associated DNA sequencing · ddRAD · Diet · Euphausia superba · Natural selection
Keywords: Bouvetøya; Sørishavet; genetikk; krill; marin biologi; pelsseler; plankton; zoologi; økosystemer

Temporal shift in the isotopic niche of female Antarctic fur seals from Bouvetøya - Tarroux, Arnaud; Lowther, Andrew D; Lydersen, Christian; Kovacs, Kit M. (Polar Research, 2016)
The Antarctic fur seal (Arctocephalus gazella) is a key marine predator in the Southern Ocean, a region that has recently started to show changes as a result of global climate change. Here, carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope analyses on whole blood and plasma samples were used to examine the isotopic niche of lactating female Antarctic fur seals. Using recently developed Bayesian approaches to determine changes in isotopic niche, a significant increase in δ 13 C and δ 15 N was found between 1997 and 2015; this change occurred at an average rate of 0.067‰ (δ 13 C) and 0.072‰ (δ 15 N) per year over this period. This suggests that a marked isotopic niche shift has occurred over this period, which very likely corresponds to a shift in diet towards prey at a higher trophic level, such as fish (replacing krill). Although our sampling design prevented us from exploring a seasonal trend in a conclusive manner, our data suggest that concurrent increases in δ 13 C and δ 15 N might occur as the breeding season progresses. At a seasonal scale, an average decrease of −0.7‰ per month (95% confidence interval=[−0.9; −0.6]) in δ 13 C might have occurred, concurrently with an average increase of 1.1‰ per month in δ 15 N. The results of this study constitute the first isotopic assessment for female Antarctic fur seals from Bouvetøya and provide a baseline for the use of this predator species as a sentinel of the marine trophic system in one of the least studied areas within this species' distributional range.
Keywords: Bouvetøya; Sørishavet; klimaendringer; krill; marin biologi; pelsseler; plankton; stabile isotoper; zoologi

Reliability of VHF telemetry data for measuring attendance patterns of marine predators: a comparison with time depth recorder data - Lowther, A D; Ahonen, H; Hofmeyr, G; Oosthuizen, W C; De Bruyn, P J N; Lydersen, C; Kovacs, K M (Marine Ecology Progress Series, 2015)
Very high frequency (VHF) radiotelemetry data has been used for over 30 yr to monitor the behavior patterns of otariid seals. These data have been used in a wide variety of ways, from characterizing the reproductive and foraging ecology of these species to inferring ecosystem changes based on variation in attendance patterns. Yet the accuracy of VHF data has never been appropriately evaluated. Our study compares VHF data collected on 16 lactating Antarctic fur seals to assess onshore attendance with concurrently collected time depth recorder (TDR) data used as the true measurement of time spent onshore. Within the retrieved datasets, 25% of the VHF data could not be interpreted with any reliability. Additionally, there were significant differences in the number and duration of attendance bouts between the 2 instrument types, with VHF data overestimating attendance bout duration by approximately 8.9 h on average. Importantly, the magnitude and direction of errors between VHF and TDR measurements were not systematic, suggesting that VHF data is an inappropriate method for collecting attendance data. Modelling the raw VHF data in a state-space framework elicited mean attendance durations that were indistinguishable from TDR-derived measurements, suggesting this approach may provide a means to re-examine historic VHF data. Moreover, given the evolution of electronic tags in terms of sophistication, miniaturization, longevity and decreasing cost over the last 30 yr, TDRs are a more appropriate means of collecting attendance data on centrally foraging marine mammals such as otariids.
Keywords: Bouvetøya; NARE ekspedisjoner; Sørishavet; marin zoologi; overvåking; pelsseler; pinnipedier; radio telemetri; økosystemer

Instrumentation and handling effects on Antarctic fur seals (Arctocephalus gazella) - Blanchet, Marie-Anne; Lydersen, Christian; Biuw, Martin; de Bruyn, P J Nico; Hofmeyr, Greg; Krafft, Bjørn A.; Kovacs, Kit M. (Polar Research, 2014)
The use of biologging instruments has greatly improved our understanding of the behaviour, physiology and ecology of free-ranging marine mammals. However, handling wild animals and attaching instruments to streamlined bodies can cause stress and potentially influence behaviour and swimming/diving energetics. The goals of this study, undertaken on Bouvetøya, were (1) to determine if the first trip to sea after instrumentation is representative of subsequent trips in lactating Antarctic fur seals, to explore potential handling effects and assess possible biases in having multiple short-duration deployments (inflating N, using a limited number of tags) and (2) to evaluate potential effects of two different instrument combinations (SMRU satellite data relay loggers and very high frequency radio transmitters versus Wildlife Computers time–depth recorders and very high frequency radio transmitters) on trip durations, dive parameters, female body condition and pup growth. Handling did not appear to have any effects on the parameters studied; data from the first and second trips did not differ significantly. This implies that multiple short-term deployments are unlikely to result in biased data in this species. Instrument type did have measurable effects; time-at-sea was greater and pup growth was lower for pairs in which mothers carried bulkier instruments. This suggests that instrument streamlining is important to avoid negative impacts and that bulkier equipment should be deployed on lactating females with caution and only for short periods. The study highlights that instrument effects should be taken into account when comparing data from experiments collected using different equipment packages. Keywords: Bioenergetics; biologging; instrument effects; SRDLs; TDRs; VHFs.
Keywords: Bouvetøya; NARE ekspedisjoner; analyser; bioenergetikk; biologging; marin zoologi; pelsseler

At-sea behaviour of three krill predators breeding at Bouvetøya—Antarctic fur seals, macaroni penguins and chinstrap penguins - Blanchet, Marie-Anne; Biuw, Martin; Hofmeyr, Greg; de Bruyn, P. J. Nico; Lydersen, Christian; Kovacs, Kit M. (Marine Ecology Progress Series, 2013)
Keywords: Bouvetøya; krill; pelsseler; pingviner; pinnipedier; plankton; seler; zoologi

Haul-out pattern of itinerant male Antarctic fur seals (Arctocephalus gazella) at Laurie Island, South Orkney Islands - Carlini, Alejandro R; Daneri, Gustavo A; Casaux, Ricardo; Márquez, María E I (Polar Research, 2006)
The seasonal haul-out pattern of itinerant male Antarctic fur seals (Arctocephalus gazella) was determined by regular counts at Mossman Peninsula, Laurie Island, South Orkney Islands, from 1996 to 2005. Small numbers of animals began to arrive at the beach in late December / early January (mean date 28 December ± 15 days, n = 10). Peak numbers of animals ashore changed considerably between seasons. In 1996, 1998 and 2001, peak numbers were registered in March (6/3, 18/3 and 6/3, respectively). Numbers peaked in 1997, 1999 and 2005 at the end of January / beginning of February (26/1, 2/2 and 28/1, respectively). In 2000, 2002, 2003 and 2004 peaks were registered in the third week of February (15/2, 22/2, 14/2 and 20/2, respectively). Peaks in numbers of seals ashore also varied between years, being minimum during 2001 (2531 individuals) and maximum during 2006 (16 610 individuals). In March 1998 the coasts of Laurie Island were surveyed by navigating inflatable boats near the shoreline; 18 haul-out places were identified. The big differences in peak numbers, as well as in the dates of peak events among years, suggest that local conditions could have an effect on the numbers of animals hauled out in a given year. It may therefore be difficult to predict trends from summer censuses in non-breeding places.
Keywords: Antarktis; pelsseler; zoologi

Entanglement of Antarctic fur seals at Bouvetøya, Southern Ocean - Greg Hofmeyr, G J; Bester, Marthán N; Kirkman, Steve P; Lydersen, Christian; Kovacs, Kit M (Marine Pollution Bulletin, 2006)
Keywords: Bouvetøya; forurensning; marin biologi; pelsseler; pinnipedier

Entanglement of Antarctic fur seals at Bouvetøya, Southern Ocean - Greg Hofmeyr, G.J.; Bester, Marthán N.; Kirkman, Steve P.; Lydersen, Christian; Kovacs, Kit M. (Marine Pollution Bulletin, 2006)
Entanglements of Antarctic fur seals Arctocephalus gazella were recorded during four summers from 1996 to 2002 at the subantarctic island, Bouvetøya. Rates of entanglement varied between 0.024% and 0.059%. These rates are low for a pinniped population and might be because of the geographic isolation of the haulout site. An apparent decrease in the levels of entanglement over the course of the study was likely due, at least in part, to the removal of entanglements by observers. At least two-thirds of entangling materials were generated by fishery sources. Since there is no known local source of anthropogenic marine pollution, seals become entangled either in waters distant from the island, or when materials drift into local waters. Significantly more subadults were found entangled than expected from the postulated population age class distribution.
Keywords: Bouvetøya; Sørishavet; marin biologi; marin forurensning; pelsseler; pinnipedier

Population changes of Antarctic fur seals at Nyrøysa, Bouvetøya - Hofmeyr, Greg; Krafft, Bjørn; Kirkman, Stephen; Bester, Marthán; Lydersen, Christian; Kovacs, Kit (Polar Biology, 2005)
Antarctic fur seal Arctocephalus gazella pup production at Nyrøysa, Bouvetøya was estimated to be approximately 15,000 per annum during each of four summers from 1996 to 2002, indicating a total population of about 66,000. While the Bouvetøya population is the second largest for this species, pup production at this site still accounts for only 2.4% of the global total. This population experienced a mean annual rate of increase of 30.6% for the period 1989–1996, perhaps due, in part, to significant immigration, but has been stable since 1996. Historical accounts of significant numbers of animals being present towards the end of the period of sealing (C.1800–1930), indicate that the geographic isolation and inaccessibility of this site may have resulted in the Bouvetøya population being one of three populations that survived a series of periods of extreme exploitation of this species.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; zoologi

Diet and estimated food consumption of Antarctic fur seals at Bouvetøya during summer - Kirkman, Stephen; Wilson, W.; Klages, Norbert; Bester, Marthán; Isaksen, Kjell (Polar Biology, 2000)
Collection and analysis of natural regurgitations and fresh scats, deposited by Antarctic fur seals at the Nyrøysa colony, Bouvetøya, during December 1998 to February 1999, afforded a comprehensive description of the dietary composition of this expanding population during the summer months. Mature, adult Euphausia superba was the staple diet of fur seals at Nyrøysa, while squid and myctophid fish appeared to be taken opportunistically. In metric tons, the total Bouvetøya fur seal population is estimated to have consumed a minimum of 14,365 t krill (representing 1.2713 × 1010 individuals of 1.13 g mass), 186 t fish, 184 t squid and 14,735 t over 3 months, but there are many possible sources of error in these estimates. It is presumed that over-indulgence in krill may cause animals to regurgitate ashore.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; zoologi